Virtue Ethics in an Anthropological Account A Review of The Subject of Virtue: An Anthropology of Ethics and Freedom - Parisa Goudarzi; Mohsen Shabani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Moral anthropology is a newfound field in interdisciplinary studies in moral philosophy and anthropology. ‘The Subject of Virtue: An Anthropology of Ethics and Freedom’ by James Laidlaw is one of the most effective books ever in this area. The author tries to approximate the boundaries of anthropology and moral philosophy. He uses notions and theories from both fields, and it makes the book to be more than a mere anthropological study. For instance, he draws the notions of virtue and freedom from moral philosophy and anthropology, respectively. As a result, the book could be regarded as a successful interdisciplinary study, which benefits from both disciplines and at the same time contributed to them methodologically. To do so, he uses philosophical resources to support anthropological researches. Laidlaw also wants to facilitate new resources in the field of moral anthropology and puts some figures like Foucault, MacIntyre, and Williams together to improve the discussion of moral anthropology.